The noninflammatory role of high mobility group box 1/toll‐like receptor 2 axis in the self‐renewal of mammary cancer stem cells. Issue 12 (22nd August 2013) - Conti, Laura; Lanzardo, Stefania; Arigoni, Maddalena; Antonazzo, Roberta; Radaelli, Enrico; Cantarella, Daniela; Calogero, Raffaele A.; Cavallo, Federica
Abstract : Cancer stem cells (CSCs) are responsible for tumor progression, metastases, resistance to therapy, and tumor recurrence. Therefore, the identification of molecules involved in CSC self‐renewal is a necessary step toward more effective therapies. To this aim, through the transcription profiling of the murine ErbB2 + tumor cell line TUBO vs. derived CSC‐enriched mammospheres, Toll‐like receptor 2 (TLR2) was identified as 2‐fold overexpressed in CSCs, as confirmed by qPCR and cytofluorimetric analysis. TLR2 signaling inhibition impaired in vitro mammosphere generation in murine TUBO (60%) and 4T1 (30%) and human MDA‐MB‐231 (50%), HCC1806 (60%), and MCF7 (50%) cells. In CSC, TLR2 was activated by endogenous high‐mobility‐group box 1 (HMGB1), inducing IκBα phosphorylation, IL‐6 and TGFβ secretion, and, consequently, STAT3 and Smad3 activation. In vivo TLR2 inhibition blocked TUBO tumor takes in 9/14 mice and induced a 2‐fold reduction in lung metastases development by decreasing cell proliferation and vascularization and increasing apoptosis. Collectively, these results demonstrate that murine and human mammary CSCs express TLR2 and its ligand HMGB1; this autocrine loop plays a pivotal role in CSC self‐renewal, tumorigenesis, and metastatic ability. These findings, while providing evidence against the controversial use of TLR2 agonists in antitumor therapy, lay out new paths toward the design of anticancer treatments.—Conti, L., Lanzardo, S., Arigoni, M., Antonazzo, R., Radaelli, E., Cantarella, D., Calogero, R. A., Cavallo, F., The noninflammatory role of high mobility group box 1/toll‐like receptor 2 axis in the self‐renewal of mammary cancer stem cells. FASEB J. 27, 4731–4744 (2013). www.fasebj.org